Synthesis of Pure Brookite Nanorods in a Nonaqueous Growth Environment - Mahmoud Hezam; Saif M. H. Qaid; Idriss M. Bedja; Fahhad Alharbi; Mohammad Khaja Nazeeruddin; Abdullah Aldwayyan (Crystals, 2019)
Brookite TiO2 is the most difficult TiO2 polymorph to synthesize. The available methods in the literature to produce brookite nanostructures mostly use water-based techniques for the preparation of water-soluble Ti complexes first, followed by a hydrothermal growth of the brookite nanostructures. Besides its multi-step nature, achieving a single brookite phase and optimizing the aqueous growth environment are all issues to be hardly controlled. In this work, pure brookite TiO2 nanorods are synthesized using tetrabutyl titanate Ti(OBu)4 and Sodium Fluoride (NaF) as precursor materials in a simple non-aqueous one-pot solvothermal process. Alcoholysis of only Ti(OBu)4 in ethanol resulted in pure anatase nanoparticles, while the addition of NaF was essential to promote the growth of highly pure brookite nanorods. The phase purity is confirmed by X-Ray Diffraction, Raman Spectroscopy, and High-Resolution Transmission Electron Microscopy. The growth mechanism is explained according to the Ostwald’s step rule, where Na+ ions are anticipated to have a potential role in driving the growth process towards the brookite phase.